2001
DOI: 10.1108/02610150110786633
|View full text |Cite
|
Sign up to set email alerts
|

African‐Americans’ perceptions of requisite characteristics of business managers

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…There is vast research done on the personal perceptions of business managers from different ethnic background. For example, Tomkiewicz, Bass, Adeyemi-Bello, and Vaicys (2001) found that African Americans perceive themselves as being less qualified to be managers than other racial groups, and such perceptions influence their behavior in both seeking managerial jobs and their performance in such jobs, thus, relatively few African Americans hold higher level managerial jobs. Wright, Martin, and Stone (2003a) looked at the issues faced by small ethnic minority businesses, their entrepreneurship orientations, their efforts at nurturing and managing relationships in building their businesses, and their attitudes to targeting their products and services.…”
Section: (C) the Influence Of Attitudes And Perceptionsmentioning
confidence: 99%
“…There is vast research done on the personal perceptions of business managers from different ethnic background. For example, Tomkiewicz, Bass, Adeyemi-Bello, and Vaicys (2001) found that African Americans perceive themselves as being less qualified to be managers than other racial groups, and such perceptions influence their behavior in both seeking managerial jobs and their performance in such jobs, thus, relatively few African Americans hold higher level managerial jobs. Wright, Martin, and Stone (2003a) looked at the issues faced by small ethnic minority businesses, their entrepreneurship orientations, their efforts at nurturing and managing relationships in building their businesses, and their attitudes to targeting their products and services.…”
Section: (C) the Influence Of Attitudes And Perceptionsmentioning
confidence: 99%